Adventitious root formation in branch cuttings of Taxus wallichiana Zucc.(Himalayan yew): A clonal approach to conserve the scarce resource - Aslam, Mohd; Raina, Parvaiz A.; Rafiq, Rouf Ur; Siddiqi, T.O.; Reshi, Zafar A. (Current Botany, 2017)
Himalayan yew (Taxus wallichiana Zucc.), is an economically valuable plant and critically endangered due to overexploitation for the isolation of Taxol,an exciting anticancer drug from its bark and leaves. Since the species is unisexual and due to its long seed dormancy period and rapid loss of viability coupled with low survival percentage, its natural regeneration from seeds is very poor. As the seed raised plants add little growth, propagation by stem cuttings was tried under natural conditions and a considerable success was achieved after making use of different auxins (Indole-3- Acetic Acid-IAA, Indole Butyric Acid-IBA and Naphthalene Acetic Acid-NAA) in different concentrations. A Randomized block design (RBD) was adopted for laying the experiment of the present study. Of the ten treatments studied, IBA at 500ppm performed best of all the treatments and registered higher callusing percentage, rooting percentage, number of roots and length of roots in the juvenile shoot cuttings of the species. The results achieved through the application ofplant growth regulators (PGRs)by way of adventitious root formation (ARF) could be useful for the management of this understory coniferous tree species, whether for conservation, habitat restoration or for the production of Taxol,a promising anti-cancer agent. The technique evolved will be the most handy, quickest, inexpensive and can be applied any where in its natural habitat for the restoration and restocking of this valuable plant, which is otherwise facing the peril of extinction throughout the range of its distribution including Indian Himalayas.